Job Satisfaction as the Main Predictor of Organizational Citizenship Behavior among Private Islamic Senior High School Teachers - Nenden Quratul Aini; Wia Adawiyah Muthoharoh; Muhammad hilmy Ibnu Muqti; Muhammad Irfan Al Anshari (CV. Edujavare Publishing, 2026)
Teachers’ willingness to perform responsibilities beyond formal job requirements is essential for improving the effectiveness of educational institutions. In Islamic senior high schools, such voluntary behaviour reflects not only professional dedication but also organizational values that encourage collaboration and mutual support. This study examines the influence of job satisfaction and organizational commitment on teachers’ Organizational Citizenship Behaviour (OCB). A quantitative explanatory design was employed using questionnaire data collected from teachers at private Islamic senior high schools. Multiple regression analysis was applied to evaluate the individual and combined effects of the independent variables on OCB. The findings reveal that job satisfaction has a significant positive effect on teachers’ OCB, whereas organizational commitment demonstrates a different level of influence when analyzed separately. Simultaneously, both variables significantly explain variations in OCB. These results suggest that teachers are more likely to engage in extra-role behaviours when they experience positive work conditions and maintain strong relationships with their institutions. The study contributes to the literature by providing empirical evidence from the context of Islamic education and highlights the importance of fostering supportive organizational environments to strengthen teachers’ voluntary contributions